Ag Nanowire‐Integrated MoS2/ZnO Heterojunctions for Highly Efficient Photogenerated Charge Transfer - Anh Thi Nguyen; Jungyoon Cho; Malkeshkumar Patel; Duc Anh Vu; Jungeun Song; Dongseok Suh; Ambrose Seo; Joondong Kim; Dong‐Wook Kim (Advanced Electronic Materials)
Abstract The integration of silver nanowire (AgNW) networks with MoS2/ZnO heterojunctions leads to a remarkable enhancement in surface photovoltage (SPV) response. In the visible wavelength range, the heterojunctions with AgNWs achieve an SPV signal of ≈200 mV, a fourfold increase compared to the counterparts without AgNWs (≈50 mV). Wavelength‐dependent nanoscopic SPV mapping suggests that this enhancement originates from efficient charge transfer between MoS2 and ZnO. Moreover, the embedded AgNWs raise the local electric potential at the MoS2 surface by several tens of mV, thereby facilitating the collection of photogenerated electrons. Optical calculations reveal that AgNWs concentrate incident light in neighboring layers across a broad wavelength range, further boosting photocarrier generation. These results, along with photoluminescence spectra, suggest that photocarrier transfer at the MoS2/ZnO heterointerfaces is significantly enhanced due to the synergistic effects of light concentration, local potential modifications, and improved electric conduction caused by the AgNW networks.